Pesticide Use Trends in the U.S.: Global Comparison - Frederick M. Fishel (EDIS)
This new series by Frederick M. Fishel provides data on volumes used and sales of pesticides from the latest EPA survey data available, 2001 - 2002. Published by the UF/IFAS Pesticide Information Office, January 2007.